Rhine low water crisis: From individual adaptation possibilities to strategical pathways - Gobert, Julie; Rudolf, Florence (Frontiers in Climate, 2023)
Introduction In 2018, the Rhine transport sector experienced an unprecedented low water crisis, during which large cargo vessels were no longer able to navigate on certain sections of the river. This led to a major disruption in inland waterway transport. This article aims at questioning how the crisis acted as a stimulus for port authorities and their customers to consider the risks for their assets and operations and as a window of opportunity for creating a new collective and for defining “solutions.” Methodology Inspired by the Impact Chain methodology, a step-by-step protocol integrating focus groups and interviews, was applied so that stakeholders affected by low waters can identify their individual and common vulnerability and define possible ways of acting (pathways). Results One of these pathways, the transitional infrastructural pathway, targets to increase the water level and overcome low water levels (use of Lake Constance as a water reservoir or creation of new water storage areas; deepening of the channel at Kaub and Maxau). It appears as the most suitable because it is a technical, well-controlled process that provides a comfortable solution in the short term. It exemplifies the lock-ins set by infrastructure. Discussion However, the participative approach also highlights the fundamental challenge of developing new processes and new intermodal organizations in the long term.